DIAMONDS—a diabetes self-management intervention for people with severe mental illness: protocol for an individually randomised controlled multicentre trial - Tim Doran; Najma Siddiqi; Simon Gilbody; Rowena Jacobs; Patrick Doherty; Catherine Hewitt; Laura Mandefield; Simon Walker; Ian Kellar; Sarah Alderson; David Osborn; Vicki Johnson; et al. (BMJ Open)
Introduction Type 2 diabetes mellitus (T2DM) is two to three times more common in people with severe mental illness (SMI) than in the general population. Supporting self-management in diabetes is fundamental to improving clinical outcomes. The DIAMONDS trial aims to evaluate the clinical and cost effectiveness of a novel, codesigned, supported diabetes self-management programme for people with T2DM and SMI.Methods and analysis This multicentre, two-armed, parallel, individually randomised controlled trial will be conducted in National Health Service mental health trusts across England. We will recruit 380 participants (≥18 years old) with a diagnosis of SMI (schizophrenia, bipolar disorder, schizoaffective disorder, psychosis and severe depression) and T2DM. Eligible and consenting participants will be randomised to the DIAMONDS intervention or treatment as usual. The intervention group will receive one-to-one sessions with a trained DIAMONDS Coach for six months. These sessions will focus on goal setting, action planning and diabetes self-management education, supported by a paper-based workbook and an optional digital application. Individuals allocated to the control group will continue to receive usual care and may be offered National Institute for Health and Care Excellence-recommended generic diabetes self-management education programmes in line with usual practice. The primary outcome is the difference in glycated haemoglobin (HbA1c) between both groups at 12 months postrandomisation. The secondary outcomes include measures of physical and mental health, diabetes complications and physical activity. Economic and process evaluations will also be performed. Outcomes will be collected at baseline and at six and 12 month post-randomisation.Ethics and dissemination This study received ethics approval by the West of Scotland Research Ethics Committee 3 (22/WS/0117). Findings will be published in peer-reviewed, academic and professional journals. We will also be producing plain language summaries, infographics and audio summaries on the website, as well as attending conferences and dissemination events. A summary of the results will be distributed to all participants and other relevant stakeholders, and we will use social media channels, websites and knowledge exchange events to communicate our findings beyond academic audiences.Trial registration number ISRCTN22275538.